1978
DOI: 10.1093/oxfordjournals.aje.a112570
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Study of Breast Cancer1

Abstract: A case-control study has been conducted in four areas of Canada in which 400 cases of breast cancer matched by age and marital status with neighborhood controls were administered medical and dietary questionnaires. The study is suggestive of an increased risk of breast cancer in post-menopausal women with younger age at menarche and an increased risk with delay of age at natural menopause. No protective effect of early age at first pregnancy was demonstrated in either pre- or post-menopausal women. An increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
55
2
1

Year Published

1981
1981
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(59 citation statements)
references
References 0 publications
1
55
2
1
Order By: Relevance
“…Apart from these, other studies showing no association between breast cancer and age at first birth have been relatively small, with less than 200 cases (Herity et al, 1975;Thein-Hlang & Thein-MaungMyint, 1978;Adami et al, 1978;Pike et al, 1981;Harris et al, 1982;Storm et al, 1986) with a low statistical power of detecting an association, especially if it was weak. Selection bias related to childbearing in the control group may explain the lack of association in the study of Choi et al (1978). Otherwise, practically all studies published since 1970 have identified late age at first childbirth as a risk factor for breast cancer.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Apart from these, other studies showing no association between breast cancer and age at first birth have been relatively small, with less than 200 cases (Herity et al, 1975;Thein-Hlang & Thein-MaungMyint, 1978;Adami et al, 1978;Pike et al, 1981;Harris et al, 1982;Storm et al, 1986) with a low statistical power of detecting an association, especially if it was weak. Selection bias related to childbearing in the control group may explain the lack of association in the study of Choi et al (1978). Otherwise, practically all studies published since 1970 have identified late age at first childbirth as a risk factor for breast cancer.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have confirmed this, but some found an additional protective effect of high parity (Soini, 1977;Tulinius et al, 1978;Paffenbarger et al, 1980;Brinton et al, 1983;Helmrich et al, 1983; Pathak et al., 1986). Others have failed to demonstrate an association between breast cancer risk and age at first birth (Choi et al, 1978; Thein-Hlaing & Thein-Maung-Myint, 1978;Adami et al, 1980;Pike et al, 1981;Harris et al, 1982;Kvale et al, 1987b).Conflicting evidence also exists in the literature regarding the role of early terminated pregnancies. Two reports (Pike et al, 1981;Hadjimichael et al, 1986) suggested that a first trimester abortion (induced or spontaneous) before the fullterm pregnancy might elevate the risk of breast cancer, while such an effect was not seen in two other studies (Vessey et al, 1982;Brinton et al, 1983).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Premenopausal breast cancer risk associated with heavier than average weight at the age of 15 or thereabouts was decreased in some studies (Coates et al, 1999;Hislop et al, 1986;Le Marchand et al, 1988a), increased in one study (Pryor et al, 1989), and had no association in other studies (Brinton and Swanson, 1992;Choi et al, 1978;Franceschi et al, 1996). The reduction in risk reported by Le Marchand et al (1988a) was for the highest tertile of body mass index compared with the lowest tertile (OR=0.45, 95% CI 0.23 -0.86).…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, high adolescent (Coates et al, 1999;Hislop et al, 1986;Le Marchand et al, 1988a), early adult (Coates et al, 1999;Huang et al, 1997;Trentham-Dietz et al, 1997) and adult weight or body mass index (Brinton and Swanson, 1992;Huang et al, 1997;Swanson et al, 1996;Ursin et al, 1995;van den Brandt et al, 2000) appear to be protective against premenopausal breast cancer. Several studies have investigated the association between breast cancer and weight at birth (De Stavola et al, 2000;Ekbom et al, 1992Ekbom et al, , 1997Innes et al, 2000;Le Marchand et al, 1988b;Michels et al, 1996;Sanderson et al, 1996Sanderson et al, , 1998a or weight at adolescence (Brinton and Swanson, 1992;Choi et al, 1978;Coates et al, 1999;Franceschi et al, 1996;Hislop et al, 1986;Le Marchand et al, 1988a;Pryor et al, 1989) with inconsistent findings. Possible limitations of these studies related to exposure measurement and age at diagnosis of breast cancer.…”
mentioning
confidence: 99%